2023
DOI: 10.1101/2023.07.06.23292311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-ancestry genome-wide meta-analysis of 56,241 individuals identifiesLRRC4C, LHX5-AS1and nominates ancestry-specific lociPTPRK,GRB14, andKIAA0825as novel risk loci for Alzheimer’s disease: the Alzheimer’s Disease Genetics Consortium

Abstract: Limited ancestral diversity has impaired our ability to detect risk variants more prevalent in non-European ancestry groups in genome-wide association studies (GWAS). We constructed and analyzed a multi-ancestry GWAS dataset in the Alzheimer Disease (AD) Genetics Consortium (ADGC) to test for novel shared and ancestry-specific AD susceptibility loci and evaluate underlying genetic architecture in 37,382 non-Hispanic White (NHW), 6,728 African American, 8,899 Hispanic (HIS), and 3,232 East Asian individuals, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…This study does have some weaknesses that need to be acknowledged. Firstly, despite a similar sample size and single variant analysis model to the work done by Rajabli et al, 24 , this study identi ed more novel associations with AD. Given the limited availability of large-scale EOAD analyses for comparison, it is challenging to entirely dismiss the possibility of false positives arising a consequence of our study design.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This study does have some weaknesses that need to be acknowledged. Firstly, despite a similar sample size and single variant analysis model to the work done by Rajabli et al, 24 , this study identi ed more novel associations with AD. Given the limited availability of large-scale EOAD analyses for comparison, it is challenging to entirely dismiss the possibility of false positives arising a consequence of our study design.…”
Section: Discussionmentioning
confidence: 65%
“…To put our trans-ancestry results in context with more recent ndings and assess our hypothesis, we can compare our ndings and conclusions with transancestry LOAD analyses by Lake et al, 25 and Rajabli et al, 24 . Lake et al, were able to identify two novel trans-ancestry LOAD loci by meta-analysis of summary statistics from ve recent LOAD GWASs; from Bellenguez 18 , FinnGen Release 6 (https://www.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This pathway is activated by Aβ in microglia, where PTK2B is autophosphorylated and generates a positive feedback loop to further activate TRPM2 [69]. PTK2B has been implicated in AD through a number of GWAS studies [4,6,[70][71][72][73][74][75][76][77]. As well as being involved in response to Aβ, PTK2B co-localizes with hyperphosphorylated Tau in the brain of AD patients and in a mouse model, and it may contribute to Tau phosphorylation [78,79].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these differences, alternative genetic risk factors might play a role in the development of AD in these populations. A recent transethnic AD genome-wide association study identified ancestry-specific loci, underscoring the need for more research into non-European populations' genetics, biomarkers, and mechanisms (Rajabli et al, 2023 ).…”
mentioning
confidence: 99%